Airway Complications during and after General Anesthesia: A Comparison, Systematic Review and Meta-Analysis of Using Flexible Laryngeal Mask Airways and Endotracheal Tubes - Xu, Rui (PLoS One, 2016)
OBJECTIVE: Flexible laryngeal mask airways (FLMAs) have been widely used in thyroidectomy as well as cleft palate, nasal, upper chest, head and neck oncoplastic surgeries. This systematic review aims to compare the incidence of airway complications that occur during and after general anesthesia when using the FLMA and endotracheal intubation (ETT). We performed a quantitative meta-analysis of the results of randomized trials. METHODS: A comprehensive search of the PubMed, Embase and Cochrane Library databases was conducted using the key words "flexible laryngeal mask airway" and "endotracheal intubation". Only prospective randomized controlled trials (RCTs) that compared the FLMA and ETT were included. The relative risks (RRs) and the corresponding 95% confidence intervals (95% CIs) were calculated using a quality effects model in MetaXL 1.3 software to analyze the outcome data. RESULTS: Ten RCTs were included in this meta-analysis. There were no significant differences between the FLMA and ETT groups in the incidence of difficulty in positioning the airway [RR = 1.75, 95% CI = (0.70–4.40)]; the occurrence of sore throat at one hour and 24 hours postoperative [RR = 0.90, 95% CI = (0.13–6.18) and RR = 0.95, 95% CI = (0.81–1.13), respectively]; laryngospasms [RR = 0.58, 95% CI = (0.27–1.23)]; airway displacement [RR = 2.88, 95% CI = (0.58–14.33)]; aspiration [RR = 0.76, 95% CI = (0.06–8.88)]; or laryngotracheal soiling [RR = 0.34, 95% CI = (0.10–1.06)]. Patients treated with the FLMA had a lower incidence of hoarseness [RR = 0.31, 95% CI = (0.15–0.62)]; coughing [RR = 0.28, 95% CI = (0.15–0.51)] during recovery in the postanesthesia care unit (PACU); and oxygen desaturation [RR = 0.43, 95% CI = (0.26–0.72)] than did patients treated with ETT. However, the incidence of partial upper airway obstruction in FLMA patients was significantly greater than it was for ETT patients [RR = 4.01, 95% CI = (1.44–11.18)]. CONCLUSION: This systematic review showed that the FLMA has some advantages over ETT because it results in a lower incidence of hoarseness, coughing and oxygen desaturation. There were no statistically significant differences in the difficulty of intubation or in the occurrence of laryngospasms, postoperative sore throat, airway displacement, aspiration or laryngotracheal soiling. However, there was a higher incidence of partial upper airway obstruction in the FLMA than in the ETT group. We conclude that the FLMA has some advantages over ETT, but surgeons and anesthesiologists should be cautious when applying the mouth gag, moving the head and neck, or performing oropharyngeal procedures to avoid partial upper airway obstruction and airway displacement. The FLMA should not be used on patients at high risk for aspiration.